Sarcoidosis of the external nose: The Role of Pharmacologic Rhinoplasty in Diagnosis and Treatment - Lee, Yan Ho; Park, Eunice; Lee, Jonathan; Lawson, William (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2018)
Subcutaneous sarcoidosis is a rare manifestation of a systemic disease.  Sarcoidosis most often affects the pulmonary system but can also affect sinonasal tissues including the cutaneous and subcutaneous layers.  It can be suspected in patients who may or may not have a prior diagnosis of sarcoidosis but who develop nodules or lesions over the nasal dorsum after trauma or rhinoplasty.  The onset may also be spontaneous with diffuse enlargement of the nose.  The diagnosis can be confirmed with tissue biopsy.  Management is primarily medical with topical, intralesional, or systemic steroids.  When medical management has failed, surgical options can be considered.  We present a total of four patients with subcutaneous nasal sarcoidosis.  Two patients had diffuse subcutaneous sarcoidosis that improved significantly with medical therapy.  Two other patients with post-traumatic nodule formation were managed with intralesional steroids and surgery.